The Integration of a Semi-Modern Pesantren Curriculum with the National Education Curriculum at Pondok Pesantren - Mohammad Fikri Rafsanjani; Saepul Mukti; Nur Fatimah; Adang Hambali; Hasan Basri (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2026)
This study aims to analyze the model, implementation strategy, and impact of the integration of the semi-modern pesantren curriculum with the national education curriculum at the Assa'adah Islamic Boarding School, Depok City. The development of national education that demands formal recognition, academic competence without eliminating the identity of classical Islamic science. This condition encourages the need to integrate the pesantren curriculum with the national education curriculum as a sustainability strategy for Islamic educational institutions. This study uses a qualitative approach with a case study method. The research subjects include pesantren leaders, teachers, and students. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies. The results of the study show that the Assa'adah Islamic Boarding School applies a parallel curriculum integration model, where the salaf pesantren curriculum and the national curriculum are carried out in an integrated institutional system. Formal learning based on the Independent Curriculum is carried out in the morning, while learning the yellow book and typical programs of pesantren is carried out in the afternoon and evening. This integration is supported by schedule synchronization, integrated curriculum structure, and the implementation of dual evaluations in the form of national report cards and pesantren report cards. Curriculum integration has a positive impact on improving the academic quality of students, forming religious and nationalist characters. This research contributes to providing an adaptive and relevant model of pesantren curriculum integration for the development of contemporary Islamic education without losing its traditional identity.